Integration of the Cambridge International Examinations (CIE) Curriculum with the National Curriculum in Primary Schools - Muhammad Naufal Zaki Zaki; Nirva Diana; Muhammad Muchsin Afriyadi (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
The development of 21st-century education demands the integration of national education standards with global competencies. Although the integration of the Cambridge International Examinations (CIE) Curriculum with the National Curriculum has been implemented in several elementary schools in Indonesia, existing research is still partial and has not presented a comprehensive synthesis of the form of integration, advantages, disadvantages, and recommendations for its implementation. This study aims to describe the form of integration of the Cambridge International Examinations (CIE) Curriculum with the National Curriculum in elementary schools and analyze the advantages and disadvantages of its implementation based on the results of previous research. The study used the Systematic Literature Review method with reference to the PRISMA guidelines. Data sources came from scientific articles obtained through the Scopus and Semantic Scholar databases with a publication range of 2022-2026. Of the 602 identified, 7 articles met the inclusion criteria for analysis. Data analysis was conducted descriptively-thematically and supported by bibliometric analysis using VOSviewer software. The results showed that curriculum integration was carried out through curriculum mapping, alignment of learning outcomes, material integration, bilingual learning, and adjustments to the assessment system. The implementation of this integration contributes to improving students' critical thinking skills, literacy, numeracy, English language proficiency, and global competency without neglecting national values. However, its implementation still faces challenges in the form of limited teacher competency, learning suggestions, dual curriculum management, and learning time allocation. This study contributes in the form of a comprehensive synthesis of the forms, benefits, challenges, and recommendations for implementing the Cambridge International Examinations (CIE) Curriculum Integration with the National Curriculum as a reference for schools, educators, researchers, and policymakers in developing curriculum in elementary school.